Penari Berhijab dalam Perspektif Masyarakat sebagai Ajang Dakwah melalui Kesenian - Muhamad Parhan; Cindy Anugrah Pratiwi; Rika Agustina; Salsa Nurul Aini (Institut Seni Indonesia Surakarta, 2022)
This article provides an overview of the implications of Islamic science and art. Not many dancers wearing hijab when dancing, because it is considered something unusual. Various stigmas appear in the perspective of society when they see dancers wearing hijab. One of the stigmas given is that women or girls wearing hijab are not supposed to dance because often the movements performed can invite lust, for instance, through erotic movements that could trigger lust especially in men who are not family members of the women. The dancers wearing hijab, on the other hand, appear to be conveying an implicit message of Islamic preaching. Every dance, in fact, has meaning and serves as a medium for the dancer’s self-actualization through movements. With this phenomenon in mind, this study was conducted to collect, conclude, and share understanding from many perspectives on hijab-wearing dancers. To obtain larger data, this study used a qualitative method with descriptive analysis. This research could be used as a reading source to open up fresh perspectives for society and to encourage hijab-wearing women to express themselves limitlessly when doing activities such as dancing.